2009
DOI: 10.1152/ajpheart.00385.2009
|View full text |Cite
|
Sign up to set email alerts
|

Speckle tracking echocardiography in the assessment of mouse models of cardiac dysfunction

Abstract: Two-dimensional (2-D) speckle tracking echocardiography (STE) accurately quantifies circumferential strain (S(circ)) and radial strain (S(rad)) in humans and in large and small animals. This study was performed to assess sensitivity of S(circ) and S(rad) to left ventricular (LV) dysfunction in mouse models. We performed 2-D and M-mode echocardiography 1) in 6 mice during superficial and profound isoflurane anesthesia, 2) serially in 12 mice to monitor the development of heart failure induced by transverse aort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
72
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 21 publications
7
72
2
1
Order By: Relevance
“…24 However, these authors observed a higher correlation for circumferential strain with interstitial fibrosis than for radial strain. 24 In a rat model of doxorubicin cardiomyopathy, Migrino et al observed an early reduction of radial strain after 8 weeks; the fractional shortening changed later, after 12 weeks.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…24 However, these authors observed a higher correlation for circumferential strain with interstitial fibrosis than for radial strain. 24 In a rat model of doxorubicin cardiomyopathy, Migrino et al observed an early reduction of radial strain after 8 weeks; the fractional shortening changed later, after 12 weeks.…”
Section: Discussionmentioning
confidence: 92%
“…STE has been used to gain further insight into the pathophysiology of cardiac ischemia and infarction, and several primary diseases of the myocardium, such as hypertrophic or diabetic cardiomyopathy. [16][17][18] It has recently been appreciated that STE can also be used to identify areas of myocardial fibrosis, [19][20][21][22][23][24] one of the hallmarks of UC. This prompted us to evaluate in an animal study whether STE can detect early changes of left ventricular function and correlates with histologically determined severity of myocardial fibrosis in rat models of UC.…”
mentioning
confidence: 99%
“…Currently, 2DST is available to detect regional myocardial deformation in various cardiac diseases. [3][4][5][6][7][8][9] Furthermore, the sensitivity of high-frame 2DST in the circumferential direction was recently assessed in rat and mouse models with very thin myocardial thickness, 12,13 and this technique can be used in the clinical setting. Therefore, we applied it to the carotid arterial wall, because this technique enables the measurement of strain in very thin tissue segments with high reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…However, CS was semi-automatically measured using 2DST software with high reproducibility. [3][4][5][6][7][8][9]12,13 The difference in measurement methods may account for the significantly better reproducibility of e circ compared with b. Second, e circ is a parameter Carotid arterial circumferential strain M Saito et al that directly measures the elasticity of the carotid arterial wall in the circumferential direction, whereas b is an indirect parameter that measures the change of the internal luminal diameter of the artery in the radial direction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation